Ability and Achievement Variables in Average, Low Average, and Borderline Students and the Roles of the School Psychologist - Claypool, Tim; Marusiak, Christopher; Janzen, Henry L. (Alberta Journal of Educational Research, 2008)
This study contributes to ongoing research in the field of school psychology by examining some of the effects of using the Full Scale Intelligence Quotient (FSIQ) to classify students aged 6-16 years according to their results on an individual measure of intelligence, the Wechsler Intelligence Scale for Children, Third Edition (WISC-III, 1991). Levels of achievement in word-reading and mathematics calculation were compared for 196 students classified as Average (IQ ranging from 90-109), Low Average (IQ ranging from 80-89), or Borderline (IQ ranging from 70-79). In all cases the Low Average and Borderline groups’ achievement levels differed significantly from that of the Average group. The fact that reading and mathematics abilities were not differentiated when Low Average and Borderline groups were compared calls into question the veracity of these labels.